O trabalho do professor de matemática: a confluência da experiência profissional com a formação acadêmica - Castro, Franciana Carneiro de (2010)
This study aims at investigating and analyzing the confluence of the professional experience with academic formation, identifying the process of mobilization and resignification of the teaching work of a group of student-teachers who teach Mathematics. Therefore, it is based on a theoretical framework that allows for the analysis of the relationship between formal studies of Mathematics teachers and professional experience, with emphasis on the concepts of formation, work, teaching knowledge, experience and professional development. The methodological process of research is developed on an investigative path that allows the mixed mode of data analysis, i.e. quantitative and qualitative. In the first phase, 43 student-teachers take part as research subject, and in the second, 8 student-teachers. Data collection is done through instruments such as: registration form, questionnaire, interview and materials (report and memorial). Because of this reflection process, it is possible to notice that there was a process of mobilization and resignification of the teacher s work. In fact, the professional experience spread all over the school allowed student-teachers to resignify their professional craft based on academic background. It is expected, thus supporting the deepening of the theme, so that it can better describe the work of the trainerteacher group of professionals from which this researcher is a member and perhaps to provide graduates and students of the Mathematics bachelor degree with a more theoretical support on the pedagogical practice of the Mathematics teacher in the classroom